Characterization, crystal structure and cytotoxic activity of a rare iridoid glycoside from Lonicera saccata. Issue 3 (18th February 2020) - Qu, Zhaoxia; Ma, Li; Zhang, Qi; Yang, Renyong; Hou, Guige; Wang, Yanan; Zhao, Feng
Abstract : A new iridoid glycoside with a rare structure having a glycosyl moiety at C‐3 was obtained from Lonicera saccata, and its structure was established by spectroscopic methods and single‐crystal X‐ray diffraction. Its cytotoxic activity was evaluated by the MTT method. Abstract : A new iridoid glycoside, methyl (3 R, 4 R, 4a S, 7 S, 7a R )‐3‐hydroxy‐7‐methyl‐5‐oxooctahydrocyclopenta[ c ]pyran‐4‐carboxylate‐3‐ O ‐β‐d ‐(1′ S, 2′ R, 3′ S, 4′ S, 5′ R )‐glucopyranoside, named loniceroside A, C17 H26 O10, (1 ), was obtained from the aerial parts of Lonicera saccata . Its structure was established based on an analysis of spectroscopic data, including 1D NMR, 2D NMR and HRESIMS, and the configurations of the chiral C atoms were determined by X‐ray crystallographic analysis. The single‐crystal structure reveals that the cyclopenta[ c ]pyran scaffold is formed from a five‐membered ring and a chair‐like six‐membered ring connected through two bridgehead chiral C atoms. In the solid state, the glucose group of (1 ) plays an important role in constructing an unusual supramolecular motif. The structure analysis revealed adjacent molecules linked together through intermolecular O—H…O hydrogen bonds to generate a banded structure. Furthermore, the banded structures are linked into a three‐dimensional network by interesting hydrogen bonds. Biogenetically, compound (1 ) carries a glucopyranosyloxy moiety at the C‐3 position, representing a rare structural feature for naturally occurring iridoid glycosides. The growth inhibitory effects against human cervical carcinoma cells (Hela), human lung adenocarcinoma cells (A549), human acute mononuclear granulocyte leukaemia (THP‐1) and the human liver hepatocellular carcinoma cell line (HepG2) were evaluated by the MTT method.